2018
DOI: 10.1101/408369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulating CRISPR gene drive activity through nucleocytoplasmic localization of Cas9 in S. cerevisiae

Abstract: The bacterial CRISPR/Cas genome editing system has provided a major breakthrough in molecular biology. One use of this technology is within a nuclease-based gene drive. This type of system can install a genetic element within a population at unnatural rates. Combatting of vectorborne diseases carried by metazoans could benefit from a delivery system that bypasses traditional Mendelian laws of segregation. Recently, laboratory studies in fungi, insects, and even mice, have demonstrated successful propagation of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In this regard, Roggenkamp et al [109] reported the drive activity to be contingent on four conserved features: the Cas9 protein level, the sgRNA uniqueness, the Cas9 nucleocytoplasmic shuttling, and lastly, the novel Cas9-Cas9 tandem fusions. In their latest study, Goeckel et al [110] expanded upon their previous work to assess the ability to modulate the nuclease activity of Cas9 in S. cerevisiae based on its nucleocytoplasmic localization. Authors examined nonnative nuclear localization sequences (both nuclear localization signal (NLS) and BioDesign Research nuclear export signal (NES)) on Cas9 fusion proteins and demonstrated that mutational substitutions to nuclear signals and combinatorial fusions could modulate the gene drive activity within a cell population [110].…”
Section: Applications In Microorganismsmentioning
confidence: 99%
“…In this regard, Roggenkamp et al [109] reported the drive activity to be contingent on four conserved features: the Cas9 protein level, the sgRNA uniqueness, the Cas9 nucleocytoplasmic shuttling, and lastly, the novel Cas9-Cas9 tandem fusions. In their latest study, Goeckel et al [110] expanded upon their previous work to assess the ability to modulate the nuclease activity of Cas9 in S. cerevisiae based on its nucleocytoplasmic localization. Authors examined nonnative nuclear localization sequences (both nuclear localization signal (NLS) and BioDesign Research nuclear export signal (NES)) on Cas9 fusion proteins and demonstrated that mutational substitutions to nuclear signals and combinatorial fusions could modulate the gene drive activity within a cell population [110].…”
Section: Applications In Microorganismsmentioning
confidence: 99%
“…Our previous work in yeast has employed use of the type II S. pyogenes Cas9 to power gene-drive systems within diploid cells [24][25][26]28]. Given the discovery and widespread availability of other CRISPR nucleases and engineered variants, we predicted that use of alternative systems may also allow for successful gene-drive (GD) activity in vivo.…”
Section: Design Of Crispr Gene-drive System In S Cerevisiae Using F N...mentioning
confidence: 99%
“…To date, these systems have been developed and studied in fungi, metazoans, bacteria and viruses under laboratory conditions [18,19,[21][22][23]. Our previous work has developed a safe and 'artificial' drive system in budding yeast for study of various aspects of CRISPR/Cas editing such as nucleocytoplasmic trafficking, guide RNA specificity and anti-CRISPR inhibition [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Halder and colleagues developed an optimized protocol for CRISPR based gene-drive system to study genetic interactions in C. albicans [ 45 ]. Furthermore, improvements in CRISPR-Cas9 gene drives have been developed providing means to markerless-selection, bias towards homology-directed repair, increased layers of biosafety, maximizing potential redundancy and regulating gene-drive activity [ 39 , 41 , 42 , 46 ].…”
Section: Crispr/cas Gene Editingmentioning
confidence: 99%